(n+5)(n-9)=18

Simple and best practice solution for (n+5)(n-9)=18 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (n+5)(n-9)=18 equation:


Simplifying
(n + 5)(n + -9) = 18

Reorder the terms:
(5 + n)(n + -9) = 18

Reorder the terms:
(5 + n)(-9 + n) = 18

Multiply (5 + n) * (-9 + n)
(5(-9 + n) + n(-9 + n)) = 18
((-9 * 5 + n * 5) + n(-9 + n)) = 18
((-45 + 5n) + n(-9 + n)) = 18
(-45 + 5n + (-9 * n + n * n)) = 18
(-45 + 5n + (-9n + n2)) = 18

Combine like terms: 5n + -9n = -4n
(-45 + -4n + n2) = 18

Solving
-45 + -4n + n2 = 18

Solving for variable 'n'.

Reorder the terms:
-45 + -18 + -4n + n2 = 18 + -18

Combine like terms: -45 + -18 = -63
-63 + -4n + n2 = 18 + -18

Combine like terms: 18 + -18 = 0
-63 + -4n + n2 = 0

Begin completing the square.

Move the constant term to the right:

Add '63' to each side of the equation.
-63 + -4n + 63 + n2 = 0 + 63

Reorder the terms:
-63 + 63 + -4n + n2 = 0 + 63

Combine like terms: -63 + 63 = 0
0 + -4n + n2 = 0 + 63
-4n + n2 = 0 + 63

Combine like terms: 0 + 63 = 63
-4n + n2 = 63

The n term is -4n.  Take half its coefficient (-2).
Square it (4) and add it to both sides.

Add '4' to each side of the equation.
-4n + 4 + n2 = 63 + 4

Reorder the terms:
4 + -4n + n2 = 63 + 4

Combine like terms: 63 + 4 = 67
4 + -4n + n2 = 67

Factor a perfect square on the left side:
(n + -2)(n + -2) = 67

Calculate the square root of the right side: 8.185352772

Break this problem into two subproblems by setting 
(n + -2) equal to 8.185352772 and -8.185352772.

Subproblem 1

n + -2 = 8.185352772 Simplifying n + -2 = 8.185352772 Reorder the terms: -2 + n = 8.185352772 Solving -2 + n = 8.185352772 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + n = 8.185352772 + 2 Combine like terms: -2 + 2 = 0 0 + n = 8.185352772 + 2 n = 8.185352772 + 2 Combine like terms: 8.185352772 + 2 = 10.185352772 n = 10.185352772 Simplifying n = 10.185352772

Subproblem 2

n + -2 = -8.185352772 Simplifying n + -2 = -8.185352772 Reorder the terms: -2 + n = -8.185352772 Solving -2 + n = -8.185352772 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + n = -8.185352772 + 2 Combine like terms: -2 + 2 = 0 0 + n = -8.185352772 + 2 n = -8.185352772 + 2 Combine like terms: -8.185352772 + 2 = -6.185352772 n = -6.185352772 Simplifying n = -6.185352772

Solution

The solution to the problem is based on the solutions from the subproblems. n = {10.185352772, -6.185352772}

See similar equations:

| x^2+3x=400 | | 9+-3k=17+2k | | 0=x^2-6x+13 | | 10=x(x+3) | | -10=8+9x | | 6(2x-3)+4(7-x)=26 | | -1/4+1/2=1/4x-5/8 | | 18x^2+5+15=0 | | 400=x(x+3) | | 4(3x+1)=3(5x-4) | | R=5m+n | | 0.06(x-10)=0.03x | | 5(8x+7)=35 | | 16=p+8-5p | | T-(-16)=19 | | 10+5b=7b-10 | | b^2+14b=-48 | | 3(x-1)=2+0.5x | | 0.6x+1.2=5.4 | | -3+5x+9=47 | | x=6y-z | | 3(x+2)=2(2x-5) | | 3+6=9(2x-3) | | 20+c=4c+-7 | | T^2*p-2T*p=0 | | 2x+4+3x+23=4x+1 | | 3x+2(4x-2)+1=19 | | 5x+3(4x+2)=125 | | 0.25x=0 | | 2a+14+-7=9 | | x-11=-5x+13 | | 0.3x-0.7=0.2 |

Equations solver categories